MENINGKATKAN KREATIVITAS SISWA MELALUI PENGGUNAAN METODE OUTDOOR LEARNING BERBANTUAN MEDIA LINGKUNGAN SEKITAR SEKOLAH PADA KELAS IV SEKOLAH DASAR: Retno Nabillah Putri, Yantoro, Issaura Sherly Pamela - retno nabillah Putri; Yantoro Yantoro; Issaura Sherly Pamela (Jurnal Tunas Pendidikan, 2023)
The type of research used in this research is Classroom Action Research. This research aims to describe the application of the Outdoor Learning Method in increasing student creativity with the help of environmental media around the school in class IV elementary school at SDN 165/I Singkawang. Based on the results of the research that has been carried out, the results show that the application of the Outdoor Learning method in increasing student learning creativity in science subjects for class IV students at SDN 165/I Singkawang has been implemented well. Implementation of the Outdoor Learning method makes fourth grade students more active and increases courage. Students explore their own knowledge by observing and asking friends and teachers. The completion or follow-up stage of implementing Outdoor Learning is in the form of evaluation and understanding of the material they have studied. As a follow-up to the implementation of Outdoor Learning, they held group discussions and presented them in front of the class. The results of this research were that the first cycle of the first meeting was 45.86% in the "Less Creative" category, the first cycle of the second meeting was 57.75% in the "Less Creative" category with an increase of 11.87%. In cycle II, the first meeting was 65.17% in the "Quite Creative" category with an increase of 7.42% and the second meeting was 71.20%, an increase of 6.03%. From the results of this research, it can be concluded that the Outdoor Learning method assisted by environmental media around the school can increase the creativity of class IV students at SDN 165/I Singkawang. This is proven by the increase in each indicator of creativity in each meeting cycle.